2010
DOI: 10.6063/motricidade.6(4).137
|View full text |Cite
|
Sign up to set email alerts
|

Reprodutibilidade de um protocolo de esforço durante a corrida em piscina funda

Abstract: RESUMODiversos protocolos são utilizados a fim de obter o esforço máximo por meio da corrida em piscina funda (DWR). Entretanto, poucos estudos analisaram a validade e reprodutibilidade em testes incrementais com a DWR. Assim, o objetivo deste estudo foi verificar a reprodutibilidade interavaliador de um protocolo durante a corrida em piscina funda. Em uma pesquisa comparativa e correlacional, 20 universitários fisicamente ativos (21.10 ± 1.68 anos, 68.90 ± 7.24 kg, 174.60 ± 5.35 cm, Σ7DC 106.80 ± 28.63 mm) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
1
3
0
1
Order By: Relevance
“…As for the results presented in Table 1, we can observe linearity in the increase in heart rate according to the progression of stages in a deep pool running protocol (Silva et al, 2010) . On the other hand, the significant differences verified in two of the HR stages, in Stage 1, possibly occurred due to the second day of tests, since participants would already be adapted to the protocol and thus performed the movement better (Coelho et al, 2007) .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…As for the results presented in Table 1, we can observe linearity in the increase in heart rate according to the progression of stages in a deep pool running protocol (Silva et al, 2010) . On the other hand, the significant differences verified in two of the HR stages, in Stage 1, possibly occurred due to the second day of tests, since participants would already be adapted to the protocol and thus performed the movement better (Coelho et al, 2007) .…”
Section: Discussionsupporting
confidence: 61%
“…On the first day, the university students received explanations about the procedures and started by keeping the body submerged only with the head above the water for 5 minutes to stabilize their heart rate. The participants who had experience in the aquatic environment, were familiarized with the running test with a 2-minute warm-up at 80 cycles per minute (CPM) (Silva et al, 2010), a measure referring to the steps performed in the water by the evaluated person . A metronome with visual signals that flash at the speed proposed by the protocol helped in the cadence of the rhythm of each stage.…”
Section: Methodsmentioning
confidence: 99%
“…33 , 34 The results obtained in this study of non-expert swimmers were similar to those observed in water running tests in deep-water pools. 25 , 35 The calculation of maximum heart rate, estimated by Karvonen (ie, 220 – age), 37 may also be useful in predicting if the swimmer, at the end of the Progressive Swim Test, was within the zone of maximum effort training; AHR in the first and second day was 88% and 89% maximum, respectively, showing that such a test required a performance of intense form by the swimmer seeking to keep up with the speed controlled by progressively more frequent beeps in each lap.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this study did not prevent quantitative reproduction of a new test for this category of swimmers, which can be observed in other studies. 15 , 23 – 25 …”
Section: Methodsmentioning
confidence: 99%
“…Com o deslocamento da lona da esteira e consequentemente do corpo do voluntário na mesma direção cria-se uma força de atrito na direção oposta ao movimento. Com o incremento da velocidade o tronco necessita se inclinar para frente, para manter o controle postural e resistir à resistência da água.Sabe-se que os exercícios aquáticos em posição vertical são utilizados por diversos profissionais da área da saúde, devido aos inúmeros benefícios proporcionados29 . Entretanto, as propriedades físicas da água devem ser devidamente consideradas antes de qualquer intervenção, pois o corpo em movimento na água sofre a ação da viscosidade, da turbulência e da velocidade 2 .…”
unclassified